Diagnostic and Prognostic Value of Electromyographic Studies in Peripheral Nerve Injury - Gupta, P.K.; Kotwal, P.P.; Bhatiya, M.; Mittal, R.; Shrestha, N.M. (Birat Journal of Health Sciences, 2017)
Introduction Electro diagnostic studies provide the surgeons with critical information regarding the location, severity and nature of a nerve injury and also useful in predicting and assessing improvement during treatment either conservatively or surgically . Objective To evaluate the role of diagnostic and prognostic value of Electromyographic (EMG) studies in Peripheral Nerve injury. Methodology Fifty patients, having peripheral nerve injury were evaluated clinically and electro-physiologically to determine the role played by the latter in the management of such injuries. The study was prospective cohort study conducted at All India Institute of medical sciences, New Delhi. Results The most common mode of nerve injury was transection(54%) and most common nerve involved was radial (38%). The most common types of nerve injury in our study were axonotmesis (42%). Nature of injury was evaluated clinically and electrophysiologically. Consclusions Electromyographic studies in peripheral nerve injury are helpful in diagnosing nerve injury, in localizing the site of injury and in estimating the extent of injury. EMG studies cannot give correct prognostic or quantify the functional recovery, but act as a useful modality to decide for re-exploration in operated cases. Birat Journal of Health Sciences 2016 1(1): 65-70